Comparative evaluation of cortical bone thickness and total alveolar width in maxillary anterior dentition pre and post levelling and alignment in patients with class I and class II molar relation treated with pre-adjusted edgewise using CBCT- in vivo com - kerudi, Veerendra; Patil, Jay Prakash; pawar, Aditi Rajesh; Tamgadge, Shrutika; nimbalkar, Sauravi; sonwane, Rushikesh (Journal of Neonatal Surgery, 2025)
Background: Orthodontic tooth movement is achieved through bone remodelling of the alveolar process .The effect of orthodontic treatment on changes in alveolar bone thickness have indicated that orthodontic tooth movement can decrease the bone thickness around the teeth. Materials and method: 20 patients were selected and further divided into 2 groups according to the skeletal and dental malocclusion; each group comprising of 10 patients.Group 1: Skeletal class I mal-occlusion and Angles class I molar relation,Group 2: Skeletal class II malocclusion and Angles class II molar relation.The cortical bone thickness and total alveolar width in maxillary anterior dentition was evaluated using pre treatment CBCT. The measurments were taken at 3mm ,6mm,9mm from CEJ(16). After completion of levelling and alignment with superelastic .014 , .016 round niti , 19*25 rectangular niti and 19*25 SS ; CBCT of these patients was taken and the cortical bone thickness and total alveolar width was measured. Results: Comparision of difference in pre and post alveolar bone thickness for both the group class I and class II Subject at 3mm,6mm and 9mm was done,The P ≤ 0.005 was considered statistically significant. The labial cortical bone,palatal cortical plate and alveolar width was significantly(p ≤ 0.001) more reduced in class II than in class I at 3mm,6mm,9mm. Conclusion” It is concluded from this study that the labial and palatal bone thickness and total alveolar width decreased significantly in class I and class II pt at 3mm 6mm and 9mm from CEJ post levelling and alignment.